Optimized simultaneous ASL and BOLD functional imaging of the whole brain. Issue 5 (24th September 2013) - Schmithorst, Vincent J.; Hernandez‐Garcia, Luis; Vannest, Jennifer; Rajagopal, Akila; Lee, Greg; Holland, Scott K.
<x xml:space="preserve">Abstract</x> Purpose To compare a double‐excitation combined arterial‐spin labeling/blood‐oxygenation level dependent (ASL/BOLD) functional imaging method to a double‐echo method. ASL provides a useful complement to standard BOLD functional imaging, to map effects of cerebral hemodynamics. Whole‐brain imaging is necessary to properly characterize large functional networks. A challenge of whole‐brain ASL/BOLD is that images for ASL functional contrast must be acquired before significant longitudinal relaxation of the inverted spins occurs; however, a longer echo time (TE) is required for optimal BOLD functional contrast, lengthening the acquisition time. Thus, existing combined ASL/BOLD studies have only partial‐brain coverage. Materials and Methods The proposed method allows acquisition of images for ASL contrast within a short period after the ASL labeling pulse and postinversion delay, then subsequent acquisition of images with longer TE for BOLD contrast. The technique is demonstrated using a narrative comprehension task in 35 normal children, and the double‐excitation method is empirically compared with the double‐echo method in 7 normal adults. Results Compared with a double‐echo sequence, simulations show the double‐excitation method improves ASL contrast‐to‐noise ratio (CNR) (∼50%) in later‐acquired slices with minimal (<1%) reduction in BOLD CNR in earlier‐acquired slices if reduced excitation flip angles for the ASL acquisitions are used. Empirical results from adult data are in agreement with the simulations. Group analyses from the narrative comprehension task also show greater intersubject sensitivity in BOLD versus ASL. Conclusion Our method simultaneously optimizes ASL and BOLD acquisitions for CNR while economizing acquisition time. J. Magn. Reson. Imaging 2014;39:1104–1117. © 2013 Wiley Periodicals, Inc.